Management of hypogonadotropic hypogonadism in men with failed puberty. Issue 2 (June 2016) - Fahmy, Ibrahim; Abdel-Salam, Mohamed A.
Abstract : Delayed, failed, or arrested puberty is the consequence of hypogonadism among adolescent boys. A variety of congenital and acquired conditions that affect the hypothalamus and/or the pituitary gland can lead to hypogonadotropic hypogonadism (HH). Congenital HH is mainly caused by genetic defects and is divided into two main categories based on the integrity of smell sensation: anosmic (Kallmann's syndrome) and normosmic isolated HH. Hormonal evaluation is the key diagnostic tool for the assessment of hypogonadism and basically includes testosterone, follicle-stimulating hormone, and luteinizing hormone. In borderline cases, several stimulation tests can be used, including luteinizing-hormone-releasing hormone, human chorionic gonadotropin, and clomiphene. Other hormones or imaging tests may be needed according to the cause and clinical presentation. Hormone replacement therapy is the main target in the treatment of HH and it includes either androgen therapy or gonadotropin-releasing hormone (GnRH)/gonadotropin therapy. Androgen replacement therapy is indicated to improve the symptoms and signs of hypogonadism. To achieve conception, GnRH or gonadotropin therapies are used. The proper time to start therapy is not well defined. At least 6–36 months of uninterrupted therapy is needed to achieve conception. Assisted reproductive techniques are indicated in case of failure to achieve conception with GnRH or gonadotropin therapy, depending on the quantity and quality of sperms and the fertility potential of the female. If azoospermia persists, testicular sperm extraction combined with intracytoplasmic sperm injection provides a successful option. Reversal of hypogonadism may occur in some patients receiving gonadotropins; thus short periods of interruption of treatment are advised.